2020
DOI: 10.3390/plants9091092
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeny of Class B Flavoprotein Monooxygenases and the Origin of the YUCCA Protein Family

Abstract: YUCCA (YUCCA flavin-dependent monooxygenase) is one of the two enzymes of the main auxin biosynthesis pathway (tryptophan aminotransferase enzyme (TAA)/YUCCA) in land plants. The evolutionary origin of the YUCCA family is currently controversial: YUCCAs are assumed to have emerged via a horizontal gene transfer (HGT) from bacteria to the most recent common ancestor (MRCA) of land plants or to have inherited it from their ancestor, the charophyte algae. To refine YUCCA origin, we performed a phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…In the observed structure, the active site appears completely inaccessible, except for the NADPH binding site, where a cavity grants the NAD­( P )H to reach the flavin. In BVMOs and NMOs (recently inserted in the same phylogenetic group of type II FMOs), the NAD­(P) + occupies this pocket for the complete catalytic cycle; , therefore, it is very likely that the substrate enters the active site on a different way. A triangular-shaped helical structure (residues 370–434) appears to create an opening to the active site (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In the observed structure, the active site appears completely inaccessible, except for the NADPH binding site, where a cavity grants the NAD­( P )H to reach the flavin. In BVMOs and NMOs (recently inserted in the same phylogenetic group of type II FMOs), the NAD­(P) + occupies this pocket for the complete catalytic cycle; , therefore, it is very likely that the substrate enters the active site on a different way. A triangular-shaped helical structure (residues 370–434) appears to create an opening to the active site (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The adjacent KS 0 domain is then hypothesized to shuttle the glycine thioester to the OxiC ACP domain where the OX domain of OxiB oxidizes the glycine amino group to the corresponding oxime via a hydroxylamine and nitroso intermediate. Sequence alignments and phylogenetic analysis revealed that the OX domain belongs to the class B flavoprotein monooxygenases (FMOs) which contain two Rossman folds, one for the binding of FAD and one for NADPH, as well as a characteristic FMO sequence motif (FxGxxxHxxxY) (Figure S33A) [29, 30] . Within the class B FMOs, the OxiB OX domain groups together with the corresponding domains from the necroxime and lobatamide pathways in a separate clade within the type I FMO subclass (Figure S34).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence alignments and phylogenetic analysis revealed that the OX domain belongs to the class B flavoprotein monooxygenases (FMOs) which contain two Rossman folds, one for the binding of FAD and one for NADPH, as well as a characteristic FMO sequence motif (FxGxxxHxxxY) (Figure S33A). [29,30] Within the class B FMOs, the OxiB OX domain groups together with the corresponding domains from the necroxime and lobatamide pathways in a separate clade within the type I FMO subclass (Figure S34). Following oxime formation, a second KS 0 domain appended to the N-terminus of OxiD likely transfers the intermediate to the ACP domain within OxiE.…”
Section: The Oxib Ox and The Oxid Mt Domain Are Involved In Omethylox...mentioning
confidence: 99%
“…Although YUCCA flavin monooxygenases were proposed to exist in Chlorophytes (Khasin et al 2018), charophytes (Wang et al 2014), and brown algae (Bogaert et al 2019), exhaustive phylogenetic (Yue et al 2012(Yue et al , 2014Bowman et al 2017;Turnaev et al 2020), and sequence similarity network analysis (Dai et al 2013) indicate YUCCA flavin monooxygenases are a land plant innovation acquired by horizontal gene transfer from bacteria. Thus, if charophyte TAR genes can produce IPyA, IPyA may have had an IAA-independent function in the algal ancestor.…”
Section: Origin and Evolution Of The Components Auxin Biosynthesismentioning
confidence: 99%